Influence of Bacterial Competitors on Salmonella enterica and Enterohemorrhagic Escherichia coli Growth in Microbiological Media and Attachment to Vegetable Seeds - Da Liu; Ronald Walcott; Kevin Mis Solval; Jinru Chen (Foods, 2021)
Interests in using biological agents for control of human pathogens on vegetable seeds are rising. This study evaluated whether probiotic bacterium Lactobacillus rhamnosus GG, bacterial strains previously used as biocontrol agents in plant science, as well as a selected plant pathogen could compete with foodborne human pathogens, such as Salmonella enterica and enterohemorrhagic Escherichia coli (EHEC), for growth in microbiological media and attachment to vegetable seeds; and to determine whether the metabolites in cell-free supernatants of competitive bacterial spent cultures could inhibit the growth of the two pathogens. The results suggest that the co-presence of competitive bacteria, especially L. rhamnosus GG, significantly (p < 0.05) inhibited the growth of Salmonella and EHEC. Cell-free supernatants of L. rhamnosus GG cultures significantly reduced the pathogen populations in microbiological media. Although not as effective as L. rhamnosus GG in inhibiting the growth of Salmonella and EHEC, the biocontrol agents were more effective in competing for attachment to vegetable seeds. The study observed the inhibition of human bacterial pathogens by competitive bacteria or their metabolites and the competitive attachment to sprout seeds among all bacteria involved. The results will help strategize interventions to produce vegetable seeds and seed sprouts free of foodborne pathogens.